Results of research of brain-derived neurotrophic factor level (BDNF) in the vitreous body of patients with proliferative diabetic retinopathy - Putienko, A.A.; Elhadj Emhamed Ali; Kovaleva, E.V. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Progression of the optic nerve neuropathy of diabetic genesis is currently associated with the neurotrophic factors dysfunction, in particular, brain-derived neurotrophic factor (BDNF), since it has a pronounced neuroprotective properties and plays an important role in retinal ganglion cells and their axons protection. The last studies have shown that BDNF level in blood plasma and lacrimal fluid in patients with diabetes mellitus is reduced both at non-proliferative and proliferative stages of the disease, but in the latter case, it is more expressed. The level of this factor in the vitreous body in patients with proliferative diabetic retinopathy (PDRP), who have received the intravitreal interventions, has been studied by some authors on the small number of observations. Purpose: To study the correlation between the level of BDNF in the vitreal content in PDRP-patients and certain electrophysiological indicators, characterizing the degree of the optic nerve neuropathy. Material and Methods. 70 patients with PDRP (70 eyes) were observed with positive treatment results riched after the intravitreal anatomic intervention. A haemophthalmos without epiretinal tissue was in 35 eyes (50.0%). 28 eyes (40.0%) had partial or total haemophthalmos with epiretinal membranes and traction retinal detachment. Among them, there were 38 women and 32 men. The average age of the patients was (55.7 ± 12.7). Results. The average level of the brain-derived neurotrophic factor (BDNF) in the vitreous body totalled 12.56 SD (6.32) pg/ml. BDNF content in patients with haemophthalmos was significantly higher than in patients with tractional macular detachment and traction-rhegmatogenous retinal detachment (t = 2.58, p = 0.012; t = 2.06, p = 0.045), respectively. In this, it depended on the type of diabetes, hypertensive disease, the degree of diabetes mellitus compensation and panretinal laser coagulation performance. In the study of visual evoked potentials (VEP) against flash 2 Hz and 12 Hz the latency and the amplitude of P1 prong were not reliably differing concerning the median values (> 11.42 pg/mL) BNDF level in the vitreous body. Wherein the study of VEP against patterns 1 ° and 0 ° 15 ' showed reliable reduction of the P100 wave amplitude in patients with lower BDNF (t = 2.13, p = 0.037; t = 2.97, p = 0.004). Between the level of BDNF in the vitreous body and Р100 wave amplitude against the pattern 1° (R = 0.6132, p = 0.0397) and 0° 15 ' (R =0.6724, p = 0.0232) there was found a strong direct correlation. The work also shows that the content of BDNF in the vitreous body in patients with visual acuity of 0.01-0.09 achieved after intravitreal interventions were significantly lower compared with 0.3-1.0 acuity (t = 2.13, p = 0.039). Conclusion. Thereby, with the proliferative changes progression in patients with PDRP, the level of BDNF in the vitreal cavity is reliably decreasing, which can lead to the emergence of neurodystrophic processes in the retina and the optic nerve, i.e. neuropathy. VEP pattern indicators to a certain extent reflect its content in the tissues of the eye and can be used in further research aimed to correct this compound in patients with PDRP.